The Use of Fiberglass Posts in the Restoration of a Destroyed Coronal Part of the Tooth - Gurskaya, Narmina Azad (Actual Dentistry, 2025)
The modern development of dentistry is marked by the emergence of new technologies and filling materials for the restoration of hard tooth tissues, which makes it possible to achieve optimal results in the rehabilitation of teeth with a deficiency of hard tissues. When restoring devitalized teeth after endodontic treatment, either direct or indirect restoration of their coronal part is performed. The aim of the study is to evaluate the quality of coronal restoration in devitalized teeth using fiberglass post systems fixed with flowable light-cured composite, as well as to determine the depth of polymerization of the flowable filling material in the root canal when cured with fiber-optic light guides with a focused beam. Materials and methods. The material for the study consisted of maxillary incisors from both male and female individuals aged 20-40 years, extracted due to periodontal disease. After extraction, the teeth were immediately rinsed in a saline solution and disinfected in a 6% hydrogen peroxide solution [3]. The crowns of the teeth were trepanned, creating access to the root canals. The root canals were mechanically prepared using reamers, and a post was fitted into each root canal. The post was then fixed with a flowable composite material. The post-endodontically treated teeth were sectioned with a diamond disc to create halves of the teeth. The internal surfaces of the tooth tissues were polished to achieve a smooth finish. Conclusions. The method of restoring tooth crowns using fiberglass posts with fixation in flowable light-cured composite material is recommended for widespread use. The use of this method reduces the risk of cracks forming in the root canal, thereby increasing the load-bearing capacity of the restored tooth.